2017
DOI: 10.1186/s13071-017-2468-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of lotilaner in dogs after oral administration as flavoured chewable tablets (Credelio™)

Abstract: BackgroundLotilaner (Credelio™, Elanco) is a novel isoxazoline that provides rapid speed of flea and tick knockdown which is sustained for at least 1 month following oral administration to dogs. The safety of lotilaner flavoured chewable tablets was investigated in a randomized, blinded, parallel-group design study in healthy Beagle puppies starting at 8 weeks of age. Lotilaner was administered orally once a month over 8 months at one, three and five times the upper level of the recommended dose range (of 20 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…There was no reduction in efficacy observed in dogs that vomited at approximately two hours post treatment and were not re-dosed. For lotilaner, the study confirmed the safety that has been reported from early laboratory work demonstrating a wide safety margin, including in young puppies, and from field reports ( Cavalleri et al, 2017c , Karadzovska et al, 2017 , Kuntz and Kammanadiminti, 2017 ). The safety of lotilaner has been attributed to its exclusive selective binding to insect GABA-gated chloride channel receptors while not having the capacity to bind to mammalian receptors so that potent insecticidal potency is retained along with a wide safety margin ( Rufener et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…There was no reduction in efficacy observed in dogs that vomited at approximately two hours post treatment and were not re-dosed. For lotilaner, the study confirmed the safety that has been reported from early laboratory work demonstrating a wide safety margin, including in young puppies, and from field reports ( Cavalleri et al, 2017c , Karadzovska et al, 2017 , Kuntz and Kammanadiminti, 2017 ). The safety of lotilaner has been attributed to its exclusive selective binding to insect GABA-gated chloride channel receptors while not having the capacity to bind to mammalian receptors so that potent insecticidal potency is retained along with a wide safety margin ( Rufener et al, 2017 ).…”
Section: Discussionsupporting
confidence: 81%
“…The earlier reports of these synthesized compounds and their mechanisms of action laid the groundwork for subsequent pre‐clinical studies as parasiticides, which were described in a special issue of Veterinary Parasitology in 2014 (Drag, Saik, Harriman, & Larsen, 2014; Shoop et al., 2014). Subsequent to their development as parasiticides they are now widely used throughout the world and are considered by most to be efficacious and safe, even in 8‐week old puppies (Drag et al., 2014; Kuntz & Kammanadiminti, 2017). However, despite the estimated millions of doses being given, adverse events (AE) that had previously been believed to be rare (Gaens, Rummel, Schmidt, Hamann, & Geyer, 2019; Quan et al., 1999), post‐marketing AE have been increasingly reported since the release of these products.…”
Section: Introductionmentioning
confidence: 99%
“…All three molecules are registered in several countries for the treatment of sarcoptic mange in dogs. Lotilaner has previously been shown to be an effective and safe treatment against fleas and ticks [ 30 34 ] and is licensed solely for that purpose. However, it has already been demonstrated to possess broader potent acaricidal properties against mites such as Demodex canis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%